Digital Techniques for Documenting and Preserving Cultural Heritage - Bentkowska-Kafel, Anna; MacDonald, Lindsay (Collection Development, Cultural Heritage, and Digital Humanities, 2018)
This book presents interdisciplinary approaches to the examination and documentation of material cultural heritage, using non-invasive spatial and spectral optical technologies.